Determinación de la diversidad de insectos Hymenoptera en dos niveles de conservación en el Valle de Jamboé, del cantón Zamora, provincia de Zamora - Jiménez Pintado, John Carlos (2023)
The recovery of tropical humid forests can be accomplished through ecological restoration activities, but this recovery needs to be monitored by means of indicators which are sensitive enough to environmental changes. In the present research, Hymenoptera families’ responses to two levels of conservation (areas under 12-years ecological restoration and well-conserved areas) were evaluated, in terms of abundance, diversity, and composition. Three reserves owned by Naturaleza y Cultura Internacional, located at Jamboé’s valley (Zamora Chinchipe province), were selected, and six Malaise-type traps for flying insects were set: three in the areas under ecological restoration and three in the forest areas. Traps were working for two consecutive months, with pots being replaced every two weeks. From samples, all Hymenoptera were sorted into families, and abundance, richness, families’ diversity (Shannon and Simpson indices), and functional groups’ diversity (Shannon and Simpson indices but with families sorted into four groups: herbivores, pollinators, predators and parasitoids) were compared between both conservation levels by means of a Mann-Whitney test, and assemblage compositions were compared by a non-metric multidimensional scaling. A total of 2865 Hymenoptera insects were collected, belonging to 32 families, with parasitoids clearly dominating samples (72.36% of individuals), without statistical significant differences between the two conservation levels, and even showing very different assemblages among areas. We concluded that ecosystem restoration could be working in a satisfactory way, but we recommend to identify the individuals to species level in order to dismiss the taxonomical level being interfering the results. Keywords: diversity, ecological restoration, tropical humid forest, Hymenoptera, indicators, conservation level